North East Atlantic vs. Mediterranean Marine Protected Areas as Fisheries Management Tool - Pérez-Ruzafa, Angel; García-Charton, José A.; Marcos, Concepción (Frontiers in Marine Science, 2017)
The effectiveness of management initiatives implemented in the context of the European Common Fisheries Policy has been questioned, especially with regard to the Mediterranean. Some of the analyses made to compare the fishing activity and management measures carried out in the North East Atlantic and in the Mediterranean do not take into account some of the differentiating peculiarities of each of these regions. At the same time, they resort to traditional fisheries management measures and do not discuss the role of marine protected areas as a complementary management tool. In this respect, the apparent failure of marine protected areas in the North-East Atlantic compared with the same in the Mediterranean is challenging European fishery scientists. Application of the classical holistic view of ecological succession to the functioning of fishery closures and no-use areas highlights the importance of combining both management regimes to fully satisfy both fishery- and biodiversity-oriented goals. We advocate that an optimal management strategy for designing an MPA to protect biodiversity and sustain fishing yields consists of combining a network of no-use areas (close to their mature state) with fish boxes (buffer zones maintained by fishing disturbance in a relatively early successional stage, where productivity is higher), under a multi-zoning scheme. In this framework, the importance of no-use areas for fisheries is based on several observations: (1) They preserve biological diversity at regional scale, at all levels—specific, habitat/seascape, and also genetic diversity and the structure of populations, allowing natural selection to operate. (2) They permit the natural variability of the system to be differentiated from the effects of regulation and to be integrated in appropriate sampling schemes as controls. (3) They maintain the natural size and age structure of the populations, hence maximizing potential fecundity, allowing biomass export to occur from core to regulated areas, dampening the fluctuations derived from deviations from the theoretical optimal effort in the fishing zone.